“Women’s Prison”. An Ethnographic View on Affective Relationships in a Medium Level Security Prison in Argentina - Soledad Ojeda, Natalia (Sociedad y Economía, 2013)
This paper is an approach to identify the forms in which affectivity develops insidewomen’s prisons. Such reflections are the result of an ethnographic fieldwork conductedin a Correctional Institution that houses adult women. The paper develops a refreshingoutlook on the prison´s social order, based on the assessment and understanding ofthe affectivity of the detainees: alliance, love and solidarity. An approach of this kind iscontrary to traditional perspectives, which characterize imprisonment as a confinementmarked exclusively by punishment and institutional surveillance.Keywords: